ANALISIS PERAN GURU SEBAGAI KONSELOR DALAM MENGATASI MASALAH EMOSIONAL PADA ANAK DI TK KEMALA BHAYANGKARI 55 SURAKARTA - Lailatul Mucharromah, Rosyida; Feri Faila Sufa; M. Hery Yuli Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Emotional issues in early childhood-such as tantrums, aggressive behavior, anxiety, and difficulty regulating emotions require appropriate management to prevent them from hindering a child's socio emotional development. In the context of Early Childhood Education (ECE), teachers act not only as educators but also as counselors who provide guidance to children in overcoming emotional challenges. This study aims to describe the teacher's role as a counselor and the strategies implemented to address emotional issues among young children at TK Kemala Bhayangkari 55 Surakarta. The study employs a descriptive qualitative approach using a case study strategy. The research subjects consisted of one